Transistor Base (B) Terminal Circuit as a Switch for LED Lighting: Performance Testing - Fransiskus Seda; Rochani Rochani; Otnial Anderias Mone; Diana Rachmawati (Politeknik Siber Cerdika Internasional, 2026)
Background: The rapid development of technology presents challenges in electronics education, particularly related to students’ ability to observe, identify, and test electronic components such as transistors through practical experiments. Objective: This study aims to systematically observe and measure transistor characteristics by identifying codes on the transistor body, determining voltage parameters, and analyzing LED load behavior when a transistor operates as a switch. Methods: The research employed an experimental approach using direct electrical measurements. A BC547 transistor was tested by applying incremental voltage inputs at the base terminal ranging from 2 Vpp to 4 Vpp (2, 2.5, 3, 3.5, and 4 Vpp). Measurements were conducted using a multimeter, power supply, and supporting circuit components under open-switch and closed-switch configurations. Results: In the closed-switch configuration, a voltage of 2 Vpp produced 0 A current with the LED off, while 2.5 Vpp resulted in 0 A current with dim illumination. Voltage inputs between 3–4 Vpp generated currents ranging from 0.02–0.12 A, causing the LED to illuminate brightly. In the open-switch configuration, all voltage levels resulted in 0 A current and the LED remained off, confirming switching behavior. Conclusion: The findings confirm that the BC547 transistor base terminal effectively functions as an electronic switch and amplifier. This study contributes to basic electronics learning by providing a clear, measurement-based experimental procedure and supports practical understanding for students and technicians in transistor identification and application.